Risk-adjusted performance analysis on Islamic and conventional equity unit trusts in Malaysian market / Suhaily Maizan Abdul Manaf , Siti Zulaikha Rahmat and Muhammad Faris Zaharudin - Abdul Manaf, Suhaily Maizan; Rahmat, Siti Zulaikha; Zaharudin, Muhammad Faris (Faculty of Business Management, 2011)
Unit trust has been considered as a good instrument among other investments for medium to long-term financial plans. There are many types of unit trusts offered in the unit trust market in Malaysia, including equity funds, money market funds, bond funds, hybrid funds, debt funds, commodity funds, real estate funds, and exchange traded funds. However, this study attempts to focused on the equity unit trust since this types of unit trust is most preferable among unit holders as it offers more return to the active and risk taker investors in terms of current income and capital appreciation as well as quick and easy returns. Moreover, instead of only looking at the conventional funds, this study also focused on the Islamic funds as this kind of funds increasingly growing at fast pace. Since more than 500 funds circulating in the market, it becomes more difficult for the investor to select the best fund to their investment. Therefore, the problem that arises is how the prospective investors can ascertain and measure the risk level of the unit trust particularly in terms of performance and the return of the funds. Thus, this study has the aim to determine the performance of equity unit trusts by using risk-adjusted measurement analysis, to study the level of risk and return concerned by each of the equity funds by using standard deviation (total risk), beta (systematic risk), and average return in different economic scenario, to determine performance measurement results by using Sharpe, Treynor, and Jensen Alpha index for each equity unit trusts selected in different economic scenario to standardize of using FTSE Bursa Malaysia KLCI and FTSE Bursa Malaysia EM AS Shari’ah Index as the main benchmark for conventional and Islamic risk-adjusted analysis, and FTSE Bursa Malaysia KLCI as the market index for the performance analysis, and to analyze and determine which funds that performs well to the others in different economic scenario. To that extent, this study focused on the conventional and Islamic launched equity funds that traded in the Malaysian market with the sample included 15 conventional equity funds and 10 Islamic equity funds from 11 management companies. Sharpe, Treynor, and Jensen’s Alpha model are employed is order to determine the performance of each selected equities. The data of the study is in the monthly Net Asset Value for five years period from January 2006 to December 2010.